Perbandingan Biaya dan Waktu Pekerjaan Dinding Bata Ringan Rumah Sederhana di Makassar - Gassing, Rifdah Afifah; Hartawam, Hartawan; Imriyanti, Imriyanti (Jurnal Penelitian Enjiniring, 2023)
Wall material become a fairly important part in a construction project. Wall materials continue to evolve in line with the demands of needs in achieving the most effective and efficient cost, time, quality. For this reason, developers will think about how to carry out projects in a relatively short period of time and optimize costs. Optimizing costs has a basic reference called Analisis Harga Satuan Pekerjaan (AHSP). This reference is still general, where in each place the application will be different. These differences it is felt necessary to compare with what is happening in the curent place. The goals of this study are to reveal the average comparison between real costs and AHSP costs. This research method is a direct observation method on simple housing projects in Makassar. The research conducted is a case study. This sampling technique used the Simple Random Sampling technique for the labor group. Based on the results of the study, the average worker productivity was 3.052 m2/day. Then the analysis of real costs produces an average cost is 0.016% lower than the calculation of the average AHSP cost analysis, so there is no significant difference.